Karakterisasi Geopolimer Semen Berbasis Terak Feronikel dari ANTAM Halmahera Timur dengan FTIR - Yulianti Malik (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
Slag is a solid waste that still contains several mineral elements such as Si and Al so that it can be used as an ingredient in the manufacture of cement known as geopolymer cement through the geopolymerization process. In the geopolymerization process, several parameters are used to improve the physical and mechanical properties of the geopolymer, one of which is temperature and curing time. In this research, the synthesis of geopolymer based on ferronickel slag and (NaOH 7 M + Na2SiO3 1.3 M) as a solvent has been carried out. The synthesis of geopolymer based on ferronickel slag has been successfully carried out through a geopolymerization process where the FTIR analysis shows that symmetrical (Si-O-Si) and (Al-O-Si) strain absorptions appear at wave numbers 500-700cm-1 and asymmetrical strain (Si-O-Si) -Si) at wave number 750-1000 cm -1